“Part Man, Part Machine, All Cop”: Automation in Policing - Adensamer, Angelika; Klausner, Lukas Daniel (Frontiers in Artificial Intelligence, 2021)
Digitisation, automation and datafication permeate policing and justice more and more each year – from predictive policing methods through recidivism prediction to automated biometric identification at the border. The sociotechnical issues surrounding the use of such systems raise questions and reveal problems, both old and new. Our article reviews contemporary issues surrounding automation in policing and the legal system, finds common issues and themes in various different examples, introduces the distinction between human “retail bias” and algorithmic “wholesale bias”, and argues for shifting the viewpoint on the debate to focus on both workers' rights and organisational responsibility as well as fundamental rights and the right to an effective remedy.